PENGARUH PEMBERIAN JUS BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KADAR KOLESTEROL TOTAL TIKUS PUTIH (Rattus norvegicus) JANTAN MODEL HIPERKOLESTEROLEMIA - Irma Suryani; Paramasari Dirgahayu; Brian Wasita (Jurnal Gizi Kesehatan, 2017)
Abstract Background : Hyperlipidemia is a major cause of cardiovascular disease because it can lead to narrow of the arteries. Prevalence of diseases caused by hyperlipidemia is still quite high in many countries. Some therapeutic agents of modern medicine has been available, but most of these drug give side effects and the cost is quite high. The content of the red dragon fruit has been studied, which consists of fiber and antioxidants.This study was conducted to determine the effectiveness of antihiperlipidemia red dragon fruit juice compared with atorvastatin.Methods : Experimental with pre and post group randomized controlled design. The 36 samples were divided into six groups randomly: negative control group, positive control group (induction high fat diet for 14 days), group 1(induction high fat diet for 14 days and atorvastatin 10 days), 2, 3 and 4 (induction high fat diet for 14 days and red dragon fruit juice with a variety of doses for 10 days). The levels of lipid profiles of samples were measured before and after the intervention is given. Data were analyzed with SPSS 22.0 for windows. Result : After 14 days of margarine induction, group KP, P1, P2, P3, and P4 showed significant increase (p <0,05) on the average of total cholesterol, as well as in P1 with 0,18 mg of atorvastatin. Conclusion Red dragon fruit juice has the potential antihiperlipidemia comparable to atorvastatin Key words: Red Dragon Fruit, Lipid Profile, Atorvastatin